Analisis Kimia dan Organoleptik Pada Pembuatan Abon Dari Jamur Tiram Dengan Penambahan Kepah Bakau Dari Jamur Tiram Dengan Penambahan Kepah Bakau - Trian Adimarta; Marisa Nopriyanti; Hamim Hamzah (Politeknik Negeri Ketapang, 2025)
This study aims to determine the process of making oyster mushroom floss with the addition of mangrove fronds, to determine the quality of oyster mushroom floss with the addition of mangrove fronds in terms of color, aroma, texture, and taste, as well as chemical properties such as water content and ash content. The implementation of making oyster mushroom floss with the addition of mangrove fronds with a ratio of oyster mushroom: mangrove fronds is 75%: 25%, 50%: 50%, and 25%: 75% with a mixing and oven processing method. Furthermore, product testing is carried out, using chemical analysis such as water content and ash content as well as organoleptic tests. The best treatment is determined based on organoleptic tests, namely in the treatment with a ratio of 75%: 25% followed by chemical analysis in the oven treatment of 3, 6, and 9 hours at a temperature of 60 ° C, with a water content of 10.73%, 9.73%, and 9.39%. Ash content 6.05%, 6.05%, and 6.30%.